Biosolid quality and its effect on deforested soil - Bravo Larrea, Yen Marvin (2023)
Objective:The objective of this research was to evaluate the effect of biosolids in an area of recent deforestation.Theoretical framework: Biosolids correspond to a type of organic waste resulting from different treatment processes.Method:The evaluation was carried out in 6 plots, in different sites in the same area and evaluated the growth of species height and laboratory analysis of microbiological, physical-chemical and heavy metal parameters for the soil; this to be compared with national and international regulations that regulate the use of biosolids.Results and conclusion:The growth of tree species, nutrient supply and toxicity of some parameters such as heavy metals and pathogens were identified according to treatment; as a result, the best growth in total height was obtained in plot P3, which had application of the biosolid with 26 tree species of the 124 species sampled. As for the soil, the biosolid increased the redox potential by 24% in the plots with substrate application and a low increase in Ni and Zn, trace elements that helped the growth in height of the plants due to the thickening of the roots.Implications of the research:the implications of this study compare national and international regulations, the biosolid is within the B classification (for forestry use).Originality:broadens the understanding of the effect of biosolids in areas with recent deforestation.